STRATEGI KOMUNIKASI PEMASARAN KOMUNITAS SULAP DARK ART ENTERTAINMENT DALAM MENARIK KLIEN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study discusses the marketing communication strategy of the Dark Art Entertainment magic community in attracting clients and finding out the obstacles in carrying out marketing communication strategies. The results of this study indicate that the marketing communication strategy of the Dark Art Entertainment magic community is facing competition is carried out in 3 stages, namely strategic planning, strategy implementation, and strategy evaluation. The planning stage of the marketing communication strategy carried out by the Dark Art Entertainment magic community is positioning. The second stage is the implementation of the marketing communication strategy of the Dark Art Entertainment magic community carrying out public relations activities, participating in community activities, social media marketing, street magic, the mouth of the mouth. The evaluation stage, the evaluation stage is carried out by Bolu ta' to see the results of the planning and implementation of the marketing communication strategy carried out by Bolu ta' and to be taken into consideration in fixing the marketing communication process carried out.